2019
DOI: 10.1007/978-3-030-34971-4_17
|View full text |Cite
|
Sign up to set email alerts
|

You Can’t See What You Can’t See: Experimental Evidence for How Much Relevant Information May Be Missed Due to Google’s Web Search Personalisation

Abstract: The influence of Web search personalisation on professional knowledge work is an understudied area. Here we investigate how public sector officials self-assess their dependency on the Google Web search engine, whether they are aware of the potential impact of algorithmic biases on their ability to retrieve all relevant information, and how much relevant information may actually be missed due to Web search personalisation. We find that the majority of participants in our experimental study are neither aware tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Robertson et al [137] 2019 Direct scrape Search Google Bing Ali et al [5] 2019 Carrier puppet Advertising Facebook Cano-Orón [24] 2019 Direct scrape Search Google Lai and Luczak-Roesch [97] 2019 Crowdsourcing Search Google Hussein et al [82] 2020 Sock puppets Search YouTube Ribeiro et al [134] 2020 below the links on search result pages. They found that partisan cues in the snippet text tend to amplify the partisanship of the original web page, an effect that was consistent across query topics, left-and right-leaning queries, and different types of web pages (e.g.…”
Section: Distortion In Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Robertson et al [137] 2019 Direct scrape Search Google Bing Ali et al [5] 2019 Carrier puppet Advertising Facebook Cano-Orón [24] 2019 Direct scrape Search Google Lai and Luczak-Roesch [97] 2019 Crowdsourcing Search Google Hussein et al [82] 2020 Sock puppets Search YouTube Ribeiro et al [134] 2020 below the links on search result pages. They found that partisan cues in the snippet text tend to amplify the partisanship of the original web page, an effect that was consistent across query topics, left-and right-leaning queries, and different types of web pages (e.g.…”
Section: Distortion In Searchmentioning
confidence: 99%
“…These findings could be limited to socio-political queries -as the earliest personalization audit showed, the degree of personalization varies across query categories [73]. Rather than queries for political candidates and topics, one study in New Zealand by Lai and Luczak-Roesch [97] used queries that public officials "might perform in the course of their everyday work duties. " Asking 30 participants to rate the relevance of personalized and nonpersonalized results, their findings suggest that up to 20% of relevant results were removed due to personalization.…”
Section: Distortion In Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential concern relates to the reproducibility of searches using search engines such as Google 9‐11 . That is, unlike database searches, web searches may return different results depending on the user, such that the search process is not fully reproducible 1,9‐13 .…”
Section: Introductionmentioning
confidence: 99%
“…One potential concern relates to the reproducibility of searches using search engines such as Google 9‐11 . That is, unlike database searches, web searches may return different results depending on the user, such that the search process is not fully reproducible 1,9‐13 . While this issue is widely recognised in theory, and some studies indicate it is a real concern, 14 detailed data on the extent of the variation are lacking 9,12,13 …”
Section: Introductionmentioning
confidence: 99%